2010
DOI: 10.5172/conu.2010.35.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Improving the safety and efficacy of warfarin therapy in a metropolitan private hospital: A multidisciplinary practice improvement project

Abstract: This multifaceted suite of interventions was successful in influencing clinician behaviour and improving compliance with evidence-based warfarin guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…7 In secondary care, the use of audit and feedback has shown improvements in warfarin management, and in many settings this approach has demonstrated small-to-moderate care improvement effects similar to those found in our study. 14,22 A review of the benefits of improvement collaboratives has also shown positive effects, but they too are often used alongside other interventions and it is often unclear which aspects determine success and why this is the case or otherwise. 8 Similarly, the use of ‘clinical champions’ in organisational patient safety interventions is known to be effective, and this may also have been a facilitating factor in the moderate success of the study.…”
Section: Discussionmentioning
confidence: 99%
“…7 In secondary care, the use of audit and feedback has shown improvements in warfarin management, and in many settings this approach has demonstrated small-to-moderate care improvement effects similar to those found in our study. 14,22 A review of the benefits of improvement collaboratives has also shown positive effects, but they too are often used alongside other interventions and it is often unclear which aspects determine success and why this is the case or otherwise. 8 Similarly, the use of ‘clinical champions’ in organisational patient safety interventions is known to be effective, and this may also have been a facilitating factor in the moderate success of the study.…”
Section: Discussionmentioning
confidence: 99%